Multi-layer enhanced proton exchange membrane for flow battery and preparation method of multi-layer enhanced proton exchange membrane

The proton exchange membrane for flow cells of porous reinforcement layers and fluorine-containing sulfonic acid resin layers prepared through multi-layer structure design and electrospinning technology solves the shortcomings of the existing membrane in terms of mechanical properties and proton conductivity, achieves higher electrical conductivity and lower metal ion permeability, and improves the stability and efficiency of the battery.

CN119890374APending Publication Date: 2025-04-25SHANDONG DONGYUE WEILAI HYDROGEN ENERGY MATERIAL CO LTD

Patent Information

Application Number
CN202510392039.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing proton exchange membranes for flow batteries are difficult to meet the requirements of strict scenarios in terms of mechanical properties, proton conductivity and metal ion permeability, and the film thickness unevenness and structural instability are prominent.

Method used

Using a multi-layer structural design, including alternately laminated porous reinforcement layer and functional resin layer, a porous reinforcement layer is prepared by electrospinning technology, and a multi-layer film is combined by scraping film method.

Benefits of technology

It improves the proton conduction ability and barrier metal ions penetration ability of the proton exchange membrane, improves mechanical properties and dimensional stability, extends the service life of the battery and reduces the risk of cross-contamination of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890374A_ABST
    Figure CN119890374A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer enhanced proton exchange membrane for a flow battery and a preparation method of the multi-layer enhanced proton exchange membrane, and belongs to the field of high polymer materials. Sulfonated polybenzimidazole serves as a middle reinforcing layer, fluorine-containing sulfonic acid resin serves as functional resin layers on the two sides, the reinforcing layers can be prevented from being corroded and degraded by electrolyte in a strong acid and alkali environment, the reinforcing material is prevented from being exposed, meanwhile, the porous reinforcing layer can be better combined with fluorine-containing sulfonic acid resin solutions on the two sides, and the service life of the composite material is prolonged. The resin solution is infiltrated into the porous layer, so that the swelling of the membrane is better limited; the thickness of the sulfonated polybenzimidazole porous enhancement layer accounts for 10%-40% of the thickness of the multi-layer enhanced proton exchange membrane, so that the transmission capacity, the strength performance and the dimensional stability of protons can be improved, and the comprehensive improvement of the sulfonic acid resin membrane in the aspects of ion permeation blocking, the dimensional change rate, the electric conductivity, the mechanical performance and the puncture resistance strength is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer materials, and in particular to a multilayer enhanced proton exchange membrane for a liquid flow battery and a preparation method thereof. Background Art

[0002] In order to obtain a safe, clean and large-scale renewable energy storage system, liquid flow batteries (RFBs) have achieved the storage and release of electricity with their excellent battery efficiency, fast response speed, long cycle life and unique modular design, thus attracting much attention in the field of electrical energy and chemical energy. As a key component of the VRFB system, the proton exchange membrane (PEM) plays the role of isolating the positive and negative electrolytes and provides the necessary proton transmission channels. An excellent PEM should have the characteristics of high proton conductivity, low vanadium ion permeability, excellent physical and chemical stability and low cost. Therefore, the research of PEM with excellent comprehensive performance has become a hot issue in the field of liquid flow batteries.

[0003] Perfluorosulfonic acid resin is currently the only ion exchange membrane material that can be used industrially. Its special molecular structure gives it excellent mechanical and chemical stability. At the same time, its highly water-absorbing side chains also provide it with excellent proton conductivity. The Nafion series membranes produced by DuPont in the United States are currently the most widely used ion exchange membranes for flow batteries. With the gradual development of flow battery technology, the continuous changes in the application scenarios of flow batteries have also put forward higher performance requirements for flow battery proton exchange membranes, especially the mechanical properties, dimensional change rate, proton conductivity and metal ion permeation rate of flow battery membranes under a wide temperature range. Current products can no longer meet the requirements of more stringent scenarios.

[0004] Chinese patent CN111395008A discloses a perfluorosulfonic acid resin / polyvinylidene fluoride composite electrospinning membrane and a preparation method thereof, wherein the polyvinylidene fluoride resin spinning membrane is immersed in an ethanol solution of the perfluorosulfonic acid resin and repeatedly immersed and dried to form a membrane, thereby effectively improving the mechanical strength and elongation at break of the membrane. However, the hydrophobic polyvinylidene fluoride will seriously affect the proton conduction ability of the proton membrane, and the thickness of the composite membrane cannot be controlled by repeated immersion to prepare the composite membrane, the uniformity is poor, and the distribution of the resin layer on both sides of the reinforcement layer cannot be controlled.

[0005] Chinese patent CN118932541A discloses a nanofiber support skeleton material, a proton exchange membrane and a preparation method thereof, and a fuel cell, wherein a perfluorosulfonic acid resin solution is applied to at least part of the surface of the nanofiber support skeleton material until no perfluorosulfonic acid resin solution remains on the surface of the nanofiber support skeleton material, and then dried to obtain a proton exchange membrane with a thickness of 12 microns. This film-forming method can only obtain a very thin proton exchange membrane, which is easily pierced by the graphite felt electrodes on both sides of the membrane and cannot be applied to liquid flow batteries. In addition, the thickness of the obtained proton exchange membrane is uneven, the surface is uneven, the nanofiber support skeleton may be exposed, the structure is unstable, its mechanical strength is limited, the creep resistance is poor, and the service life is short.

[0006] Therefore, developing a multilayer enhanced proton exchange membrane for high-performance liquid flow batteries with strong mechanical properties, small dimensional change rate, high proton conductivity and low metal ion permeation rate has positive practical significance for improving battery efficiency, reducing usage costs, and increasing electrolyte service life and battery cycle stability. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a multilayer enhanced proton exchange membrane for a liquid flow battery and a preparation method thereof.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is: A multilayer enhanced proton exchange membrane for a liquid flow battery is composed of alternately stacked porous reinforcement layers and functional resin layers, wherein the porous reinforcement layers are sulfonated polybenzimidazole porous reinforcement layers, and the functional resin layers are fluorinated sulfonic acid resin layers. The thickness of the porous reinforcement layers accounts for 10% to 40% of the thickness of the multilayer enhanced proton exchange membrane.

[0009] Preferably, the outermost layers of the multi-layer enhanced proton exchange membrane are all fluorinated sulfonic acid resin layers.

[0010] Preferably, the thickness of the multilayer enhanced proton exchange membrane is 20-150 μm, more preferably 30-80 μm.

[0011] Preferably, the number of layers of the sulfonated polybenzimidazole porous reinforcement layer is 1 to 10, preferably 1 to 3 layers.

[0012] Preferably, the thickness of a single layer of the sulfonated polybenzimidazole porous reinforcement layer is 5 to 50 μm, more preferably 5 to 20 μm.

[0013] Further preferably, the multi-layer enhanced proton exchange membrane for liquid flow battery consists of a porous reinforcement layer and functional resin layers on both sides thereof.

[0014] Preferably, the IEC (ion exchange capacity) of the sulfonated polybenzimidazole porous reinforcement layer is 0.5-2.5 mmol / g, the porosity is 50-98%, and the average pore size is 100 nm-600 nm.

[0015] More preferably, the sulfonated polybenzimidazole porous reinforcement layer has an ion exchange capacity of 1.0-2.0 mmol / g, a porosity of 55-95%, and an average pore size of 100 nm-500 nm.

[0016] Most preferably, the ion exchange capacity of the sulfonated polybenzimidazole porous reinforcement layer is 1.5-2.0 mmol / g, and the porosity is 65-95%.

[0017] Preferably, the single layer thickness of the fluorinated sulfonic acid resin layer is 5 to 50 μm, more preferably 10 to 25 μm, and most preferably 10 to 22.5 μm.

[0018] The present invention also provides a method for preparing the multilayer enhanced proton exchange membrane, comprising the following steps: (1) Scraping film: Scrape a layer of fluorinated sulfonic acid resin film-forming dispersion on the substrate; (2) Covering the surface of the fluorinated sulfonic acid resin film-forming dispersion with a sulfonated polybenzimidazole porous reinforcement layer; (3) coating a layer of fluorinated sulfonic acid resin film-forming dispersion on the surface of the sulfonated polybenzimidazole porous reinforcement layer in step (2); (4) Repeat steps (2) and (3) to obtain the required number of layers and thickness, and dry to obtain a multilayer enhanced proton exchange membrane.

[0019] Preferably, the substrate in step (1) is a glass plate. When preparing a three-layer enhanced proton exchange membrane, it is dried after step (3).

[0020] Preferably, the solid content of the fluorinated sulfonic acid resin film-forming dispersion in step (1) is 10-40%.

[0021] Further preferably, the fluorine-containing sulfonic acid resin includes one or more of long-chain branched and short-chain branched perfluororesins in some fluorine-containing sulfonic acid resins and perfluorosulfonic acid resins, among which long-chain branched perfluorosulfonic acid resins are preferred.

[0022] Further preferably, the ion exchange capacity of the fluorinated sulfonic acid resin is 0.5-2.5 mmol / g, and the molecular weight is 150,000-800,000; preferably, the ion exchange capacity is 0.8-1.8 mmol / g, and the molecular weight is 200,000-600,000; most preferably, the ion exchange capacity is 0.9-1.25 mmol / g, and the molecular weight is 200,000-500,000.

[0023] Preferably, the sulfonated polybenzimidazole porous reinforcement layer in step (2) is prepared by electrospinning.

[0024] Further preferably, the content of sulfonated polybenzimidazole s-PBI in the spinning solution used for electrospinning is 5-40wt%, the viscosity of the spinning solution is 50-150mPs / s, and the solvent is one or more of N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO, N,N-dimethylacetamide DMAC, and N-methylpyrrolidone NMP.

[0025] Preferably, the electrospinning conditions are: spinning voltage of 10-25 kV, spinning rate of 0.3-2.0 ml / h, spinning distance of 10-30 cm, ambient temperature controlled at 15-35 ° C, humidity of 20-80%. Because sulfonated polybenzimidazole has better solubility, the spinning diameter and pore size are controlled by controlling the solid content and viscosity of the spinning solution. When the thickness of the obtained porous reinforced material is 5-50 μm, the pore size is basically maintained at 100-500 nm.

[0026] Preferably, the purpose of the scraping in step (1) is to fill the film-forming dispersion into the interior of the porous material.

[0027] Preferably, the solvent of the fluorinated sulfonic acid resin film-forming dispersion in step (1) is selected from at least one of alcohols with 1 to 5 carbon chains, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0028] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present application adopts the alternating stacking of sulfonated polybenzimidazole porous reinforcement layer and fluorinated sulfonic acid resin layer to change the membrane structure of perfluorosulfonic acid resin proton exchange membrane, thereby improving the proton conduction capacity and metal ion permeation barrier capacity of the multilayer enhanced proton exchange membrane. The conductivity of the prepared proton exchange membrane can be increased to 120mS·cm -1 , the ion selectivity can be increased to 24.0×10 3 S·min·cm -3 , the vanadium ion permeability can be reduced to 5.0×10 -7 cm 2 ·min -1 , achieving comprehensive improvements in the sulfonic acid resin membrane's barrier barrier, dimensional change rate, electrical conductivity, mechanical properties, and puncture resistance.

[0029] (2) When used in liquid flow batteries, the multilayer reinforced proton exchange membrane with hydrophilic sulfonated PBI porous material as the reinforcement layer can effectively improve the mechanical properties and proton conductivity of the proton exchange membrane, while further reducing the water absorption and swelling of the membrane and the penetration of metal ions, thereby improving the charge and discharge efficiency and long-term cycle stability of the ion exchange membrane, reducing the cross-contamination penetration of the electrolyte and thus reducing the cost of electrolyte use, and solving the shortcomings of poor solubility and poor conductivity of PBI alone as a reinforcement material.

[0030] (3) The proton exchange membrane prepared by the present invention has a porous reinforcement layer with a high IEC, and the thickness of the porous reinforcement layer accounts for 10%-40% of the thickness of the multilayer reinforced proton exchange membrane, and has a high proton transmission capacity and excellent strength performance and dimensional stability.

[0031] (4) Sulfonated polybenzimidazole is used as the middle reinforcement layer, and fluorinated sulfonic acid resin is used as the resin layers on both sides. On the one hand, the perfluorosulfonic acid resin with excellent chemical stability on both sides can prevent the middle reinforcement layer from being corroded and degraded by the electrolyte in a strong acid and alkali environment, thereby preventing the reinforcement material from being exposed. On the other hand, the porous reinforcement layer in the middle can better combine with the perfluorosulfonic acid resin solution on both sides, allowing the resin solution to better infiltrate into the porous layer, just like a double-sided tape that only grasps the resin layers on both sides, thereby better limiting the swelling of the membrane.

[0032] (5) The porous reinforcement layer uses sulfonated polybenzimidazole, which can increase the free volume between molecular chains and improve the solubility of polybenzimidazole. During the spinning process, the solid content of the spinning solution can vary in a wider range, and the pore size and porosity can be better controlled. The sulfonate group interacts well with water, and the interfacial bonding ability with the perfluorosulfonic acid resin is significantly enhanced. It can also improve the water retention capacity of polybenzimidazole, so that the sulfonated polybenzimidazole has high proton conductivity at a lower temperature, and can still maintain the excellent vanadium resistance brought by the unique imidazole ring and amino group of polybenzimidazole itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 A scanning electron microscope (SEM) image of the sulfonated polybenzimidazole porous reinforcement layer provided in Example 6 of the present invention; Figure 2 A cross-sectional scanning electron microscope (SEM) image of a multilayer enhanced proton exchange membrane for a flow battery prepared in Example 6 of the present invention; Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the multilayer enhanced proton exchange membrane for a flow battery prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] Conductivity test equipment and method: Use an electrochemical workstation to test the conductivity of the membrane under the conditions of 25°C and 2 mol / L sulfuric acid.

[0037] Ion selectivity and vanadium ion permeability test standards: According to NB / T 42080-2023 "General Technical Conditions and Test Methods for Ion Conducting Membranes for All-vanadium Liquid Flow Batteries".

[0038] Puncture strength test equipment and methods: Using MTL-01 puncture force tester, at a temperature of 25°C and a humidity of 50-60%, the maximum load used to penetrate the sample at a speed of 100mm / min was tested. The sample size was 100mm*100mm.

[0039] The sulfonated polybenzimidazole s-PBI used in the present invention can be prepared according to the following method: (1.1) Under nitrogen atmosphere, dissolve polybenzimidazole (PBI) with a molecular weight of 400,000 in dimethyl sulfoxide and stir thoroughly until the solution becomes clear and transparent; (1.2) Add sodium hydride NaH to the transparent solution obtained in (1.1) above, with the mass ratio of PBI to NaH being 1:0.5 to 1:3, and react for 1 to 12 hours; (1.3) Add 1,3-propane sultone PS and bromohexane C to the reaction solution obtained in (1.2) and react for 8-16 hours; the mass ratio of PBI to PS is 1:2-1:4, and the mass ratio of PBI to C is 1:1-1:3; (1.4) Pour the reaction solution obtained in (1.3) into stirred acetone to precipitate a precipitate; (1.5) The precipitate is dried to obtain sulfonated polybenzimidazole s-PBI.

[0040] Sulfonated polybenzimidazoles with different IEC can be prepared by adjusting the amounts of 1,3-propane sultone PS and bromohexane C.

[0041] Specific preparation parameters are shown in Table 1: Table 1 Relevant parameters for preparing sulfonated polybenzimidazole with different IEC

[0042] The structural formula of sulfonated polybenzimidazole is as follows:

[0043] The sulfonated polybenzimidazole porous reinforcement layer of the present invention can be prepared according to the following method: The sulfonated polybenzimidazole resin is added to the N,N-dimethylformamide solvent, heated to a dissolution temperature of 25 to 120°C, and a 25wt% spinning solution is prepared. The solution viscosity is controlled at 65mPs / s and stirred at 50°C for 24h. The obtained polymer solution is then allowed to stand for 1h to remove bubbles and impurities, and the spinning solution is prepared into a porous reinforcement layer by electrospinning.

[0044] Among them, the conditions of the electrospinning method are: spinning voltage is 10-25kV, spinning rate is 0.3-2.0ml / h, spinning distance is 10-30cm, ambient temperature is controlled at 15-35℃, and humidity is 20-80%.

[0045] The porous reinforcement layers with different thickness, pore size and porosity were prepared by adjusting the spinning conditions.

[0046] The electrospinning parameters are shown in Table 2: Table 2 Electrospinning related parameters

[0047] The parameters of the prepared porous reinforcement layer are shown in Table 3: Table 3 Parameters of porous reinforcement layer Porous reinforcement layer Thickness (μm) Porosity (%) Average pore size (nm) A 5 85 500 B 5 85 500 C 5 85 500 D 10 85 200 E 20 85 100 F 10 75 200 G 10 95 200 H 10 85 200 I 10 65 200 J 25 70 80 Example 1 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 22.5μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 5μm obtained by spinning, namely the above-mentioned porous reinforcement layer A, was covered on the surface, and then a layer of 22.5μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 10% of the thickness of the multilayer enhanced proton exchange membrane.

[0048] Example 2 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 22.5μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 5μm obtained by spinning, namely the above-mentioned porous reinforcement layer B, was covered on the surface, and then a layer of 22.5μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 10% of the thickness of the multilayer enhanced proton exchange membrane.

[0049] Example 3 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 22.5μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 5μm obtained by spinning, namely the above-mentioned porous reinforcement layer C, was covered on the surface, and then a layer of 22.5μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 10% of the thickness of the multilayer enhanced proton exchange membrane.

[0050] Example 4 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 20μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 10μm obtained by spinning, i.e., the above-mentioned porous reinforcement layer D, was covered on the surface, and then a layer of 20μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 20% of the thickness of the multilayer enhanced proton exchange membrane.

[0051] Example 5 Preparation of multilayer enhanced proton exchange membrane for flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 15μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 20μm obtained by spinning, namely the above-mentioned porous reinforcement layer E, was covered on the surface, and then a layer of 15μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 40% of the thickness of the multilayer enhanced proton exchange membrane.

[0052] Example 6 Preparation of multilayer enhanced proton exchange membrane for flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 20μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 10μm obtained by spinning, namely the above-mentioned porous reinforcement layer F, was covered on the surface, and finally a layer of 20μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 20% of the thickness of the multilayer enhanced proton exchange membrane.

[0053] Figure 1 is a scanning electron microscope (SEM) image of the sulfonated polybenzimidazole porous reinforcement layer F used in this example. Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of the multilayer enhanced proton exchange membrane for flow battery prepared in this example.

[0054] Example 7 Preparation of multilayer enhanced proton exchange membrane for flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 20μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 10μm obtained by spinning, i.e., the above-mentioned porous reinforcement layer G, was covered on the surface, and then a layer of 20μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 20% of the thickness of the multilayer enhanced proton exchange membrane.

[0055] Example 8 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and prepared into a 25% membrane-forming solution. A layer of 10 μm thick perfluorosulfonic acid resin layer is scraped on a glass plate by a scraping method, and then a layer of s-PBI porous reinforcement layer with a thickness of 10 μm obtained by spinning, namely the above-mentioned porous reinforcement layer H, is coated on the upper part with a layer of 10 μm perfluorosulfonic acid resin, and then a second layer of 10 μm thick PBI porous reinforcement layer obtained by spinning, namely the above-mentioned porous reinforcement layer H, is coated on the upper part with a layer of 10 μm perfluorosulfonic acid resin to obtain a multilayer reinforced reinforced membrane having two layers of s-PBI reinforcement layers and three layers of perfluorosulfonic acid resin layers. The membrane is dried by a stepwise ascending heating method at 50°C (12 min) -90°C (12 min) -140°C (8 min), and finally a finished multilayer reinforced proton exchange membrane for liquid flow batteries is obtained, wherein the thickness of the porous reinforcement layer accounts for 40% of the thickness of the multilayer reinforced proton exchange membrane.

[0056] Example 9 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 20μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 10μm obtained by spinning, namely the above-mentioned porous reinforcement layer I, was covered on the surface, and finally a layer of 20μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 20% of the thickness of the multilayer enhanced proton exchange membrane.

[0057] Comparative Example 1 5g of perfluorosulfonic acid resin with an IEC value of 1.0 mmol / g and a molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 50μm was applied by scraping, and dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a 50μm thick liquid flow battery membrane was obtained.

[0058] Comparative Example 2 Preparation of porous reinforcement layer: Polybenzimidazole resin was added to N-methylpyrrolidone (NMP), and the polymer solution was made into a porous membrane with a thickness of 10 μm, a porosity of 85%, and an average pore size of 200 nm by electrospinning.

[0059] Spinning conditions: the concentration of the spinning solution is 30wt%, the viscosity of the spinning solution is 65 mPs / s, the spinning voltage is 25kV, the spinning rate is 1.5 ml / h, the spinning distance is 15cm, the ambient temperature is controlled at 25℃, and the humidity is 55%.

[0060] Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 20μm was scraped on a glass plate by scraping, and then a layer of 10μm thick PBI porous film obtained by spinning was covered on the surface, and then a layer of 20μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous enhanced layer accounted for 20% of the thickness of the multilayer enhanced proton exchange membrane.

[0061] Comparative Example 3 The s-PBI (IEC is 2.0) solution and the perfluorosulfonic acid resin solution are directly mixed and coated to form a film. In the mixed solution, the mass proportion of s-PBI and perfluorosulfonic acid resin is 25% each, and the thickness is 50μm.

[0062] Comparative Example 4 Preparation of multilayer enhanced proton exchange membrane for liquid flow battery: 5g of perfluorosulfonic acid resin with IEC value of 1.0 mmol / g and molecular weight of 300,000 was dissolved in 15g of N,N-dimethylformamide solvent, stirred at room temperature for 48h, allowed to stand for 24h, filtered to remove impurities, and configured into a 25% membrane-forming solution. A layer of perfluorosulfonic acid resin with a thickness of 12.5μm was scraped on a glass plate by scraping, and then a layer of s-PBI porous reinforcement layer with a thickness of 25μm obtained by spinning, namely the above-mentioned porous reinforcement layer J, was covered on the surface, and then a layer of 12.5μm perfluorosulfonic acid resin layer was coated on the upper part, and finally dried by step-by-step heating at 50℃ (12min)-90℃ (12min)-140℃ (8min), and finally a finished multilayer enhanced proton exchange membrane for liquid flow battery was obtained, and the thickness of the porous reinforcement layer accounted for 50% of the thickness of the multilayer enhanced proton exchange membrane.

[0063] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the multilayer enhanced proton exchange membrane for the liquid flow battery prepared in this comparative example.

[0064] Table 4 shows the performance data of the proton exchange membranes obtained in the above examples and comparative examples.

[0065] Table 4 Basic physical properties of different membrane samples

[0066] The thickness of the porous reinforcement layer is too high and the average pore size is too small, making it difficult for the resin solution to completely infiltrate the pores of the porous reinforcement layer, resulting in too many empty pores inside the reinforcement material, affecting the uniformity and stability of the proton exchange membrane and the puncture strength, making it easy to be pierced by the graphite felt electrode under long-term use.

[0067] Within a certain range of pore size and porosity, the proton exchange membrane has the best ion selectivity and the best interface bonding. As can be seen from Examples 6, 7, and 9, if the porosity is too large and there are too many holes, the dimensional stability, electrical conductivity, and tensile strength of the proton exchange membrane will be reduced. This is because if the porosity is too large, it is easy to cause insufficient filling of the resin solution, too many empty holes, and membrane structural defects; and if the porosity is too small, the resin solution is difficult to fill, and the infiltration between the resin solution and the porous reinforcement layer is not good, which easily leads to stratification of the proton exchange membrane, affecting the dimensional change rate, electrical conductivity, tensile lightness, vanadium ion permeability, ion selectivity, and puncture strength of the proton exchange membrane.

[0068] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A multilayer enhanced proton exchange membrane for a flow battery, characterized in that: The membrane is composed of a porous reinforcement layer and a functional resin layer alternately stacked together, wherein the porous reinforcement layer is a sulfonated polybenzimidazole porous reinforcement layer, and the functional resin layer is a fluorinated sulfonic acid resin layer. The thickness of the porous reinforcement layer accounts for 10% to 40% of the thickness of the multilayer enhanced proton exchange membrane.

2. The multilayer enhanced proton exchange membrane according to claim 1, characterized in that: The outermost layers of the multi-layer enhanced proton exchange membrane are all fluorinated sulfonic acid resin layers.

3. The multilayer enhanced proton exchange membrane according to claim 1, characterized in that: The thickness of the multilayer enhanced proton exchange membrane is 20-150 μm, the number of layers of the sulfonated polybenzimidazole porous reinforcement layer is 1-10, the single layer thickness of the sulfonated polybenzimidazole porous reinforcement layer is 5-50 μm, and the single layer thickness of the fluorinated sulfonic acid resin layer is 5-50 μm.

4. The multilayer enhanced proton exchange membrane according to claim 3, characterized in that: The thickness of the multilayer enhanced proton exchange membrane is 30-80 μm, the number of layers of the sulfonated polybenzimidazole porous reinforcement layer is 1-3, the single layer thickness of the sulfonated polybenzimidazole porous reinforcement layer is 5-20 μm, and the single layer thickness of the fluorinated sulfonic acid resin layer is 10-25 μm.

5. The multilayer enhanced proton exchange membrane according to claim 4, characterized in that: The ion exchange capacity of the sulfonated polybenzimidazole porous reinforcement layer is 0.5-2.5 mmol / g, the porosity is 50-98%, and the average pore diameter is 100nm-600nm.

6. The multilayer enhanced proton exchange membrane according to claim 5, characterized in that: The ion exchange capacity of the sulfonated polybenzimidazole porous reinforcement layer is 1.0-2.0 mmol / g, the porosity is 55-95%, and the average pore diameter is 100nm-500nm.

7. The method for preparing a multilayer enhanced proton exchange membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Scraping film: Scrape a layer of fluorinated sulfonic acid resin film-forming dispersion on the substrate; (2) Covering the surface of the fluorinated sulfonic acid resin film-forming dispersion with a sulfonated polybenzimidazole porous reinforcement layer; (3) coating a layer of fluorinated sulfonic acid resin film-forming dispersion on the surface of the sulfonated polybenzimidazole porous reinforcement layer in step (2); (4) Repeat steps (2) and (3) to obtain the required number of layers and thickness, and dry to obtain a multilayer enhanced proton exchange membrane.

8. The method for preparing the multilayer enhanced proton exchange membrane according to claim 7, characterized in that: In step (1), the substrate is a glass plate, and the solid content of the fluorinated sulfonic acid resin film-forming dispersion is 10-40%; in step (2), the sulfonated polybenzimidazole porous reinforcement layer is prepared by electrospinning.

9. The method for preparing a multilayer enhanced proton exchange membrane according to claim 8, characterized in that: The content of sulfonated polybenzimidazole s-PBI in the spinning solution used for electrospinning is 5-40wt%, the viscosity of the spinning solution is 50-150mPs / s, and the solvent used is one or more of N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO, N,N-dimethylacetamide DMAC, and N-methylpyrrolidone NMP.

10. The method for preparing a multilayer enhanced proton exchange membrane according to claim 7, characterized in that: The solvent of the fluorinated sulfonic acid resin film-forming dispersion in step (1) is selected from at least one of alcohols with 1 to 5 carbon chains, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

Citation Information

Patent Citations

  • Perfluorosulfonic acid resin / polyvinylidene fluoride composite electrospinning membrane and preparation method thereof

    CN111395008A

  • Nanofiber supporting framework material, proton exchange membrane, preparation method of proton exchange membrane and fuel cell

    CN118932541A

  • Blending membrane for all-vanadium redox flow battery and preparation method for blending membrane

    CN102881853A

  • PBI fiber membrane reinforced high-temperature-resistant composite proton exchange membrane and preparation method thereof

    CN110739476A

  • Enhanced long-life proton exchange membrane for hydrogen production by water electrolysis and preparation method of enhanced long-life proton exchange membrane

    CN116065171A

Cited By

  • Enhanced proton exchange membrane and application thereof

    CN121748452A